COVID-19 Appropriate Behaviour—Why do We Do What We Do? - Shimray, Chong; Shirol, Shrishail E (SCHOOL SCIENCE, 2020)
Nonpharmaceutical Interventions (NPIs) are actions that people and communities can take to help slow the spread of diseases. These measures aim to reduce transmission, thereby delaying the timing and reducing the size of the epidemic peak, and buying time for preparations in the healthcare system. During the current COVID-19 pandemic, the NPIs are in place, and invariably, every citizen has been practising appropriate behaviours such as hand washing with soaps—solid or liquid, using appropriate mask, maintaining social distancing, etc. However, majority of the populations are not aware of why and how such practices help. This paper sheds light on the scientific and historical context of such COVID-19 appropriate behaviours.